Multi-walled carbon nanotubes saturable absorber in Q-switching flashlamp pumped Nd:YAG laser - Mohd. Taib, Nur Athirah (Elsevier Ltd., 2016)
Passively Q-switched Nd:YAG laser pumped by flashlamp is demonstrated by using a saturable absorber made of a multi-walled carbon nanotubes-polyethylene oxide (MWCNTs-PEO) film. Two positions of the film are tested in the resonator to optimize its performance. The maximum pulsed energy obtained for the Q-switching operation is 1.68 mJ corresponding to 88.36 J electrical pump energy. The pulse duration of 83.64 ns is achieved with a peak power of 20.1 kW. A MWCNTs-PEO-film is a promising saturable absorber because of its simple cavity design, reliable and low cost fabrication compared to normal nonlinear crystal absorber.